Photometric Analysis of Propolis from the Island of Samothraki, Greece. The Discovery of Red Propolis - Papachristoforou, Alexandros; Koutouvela, Evgenia; Menexes, George; Gardikis, Konstantinos; Mourtzinos, Ioannis (My University, 2019)
Propolis presents notable and variable antioxidant activity depending on the territory and the local flora. As a result, propolis collected from areas presenting botanical diversity can become an intriguing research field. In the present study, we examined propolis from different areas of Samothraki, a small Greek island in the north-eastern Aegean Sea, considered a hot-spot of plant biodiversity. The analysis of propolis samples presented huge variability in the antioxidant activity, the total polyphenol content and the total flavonoids content. Propolis from two areas presented high antioxidant activity with a maximum at 1741.48 μmol of Trolox equivalents per gram of dry propolis weight, very high polyphenol content, 378.73 mg of gallic acid equivalents per gram of dry propolis weight, and high flavonoid content with a maximum concentration of 70.31 mg of quercetin equivalents per gram of dry propolis weight. The samples that presented the best qualitative characteristics were all red propolis which is a type that has never been reported in any part of Europe.
Keywords: Propolis; Samothraki Island; Antioxidant activity; Biological activity; Flavonoid content; Polyphenolic content